Malignant breast tumors - Deanna L. Lane (2018)
© 2013 Springer-Verlag Berlin Heidelberg. All rights reserved. Breast cancer is a commonly diagnosed malignancy in women, and its incidence increases with age. This chapter presents the most common types of breast cancer encountered in geriatric patients, including invasive ductal carcinoma, invasive lobular carcinoma, mucinous carcinoma, ductal carcinoma in situ, and papillary carcinoma. Since the incidence of breast cancer in men also increases with age, a section on male breast cancer is included. The imaging features of each entity are discussed. The role of imaging for the accurate staging of breast cancer is discussed, and an overview of the treatment of elderly breast cancer patients is provided, including information regarding surgery and radiation therapy, endocrine or hormonal therapy, and systemic chemotherapy.